Analisis Implementasi Kebijakan Pemerintah Daerah tentang Relokasi Pasar untuk Meningkatkan Good Governance - Rohman, Abd.; Bili, Soleman Renda; Lestari, Asih Widi (Prodi Sosiologi Agama, 2021)
The market relocation policy aims that better and cleaner city arrangement because in fact the presence of an inappropriate market raises several fundamental problems such as a narrow, less strategic market location, its proximity to gas stations, and traffic congestion. Unfortunatelly, many problems happen because of policies regarding market relocation implementation. This study uses a quantitative approach with the technique of determining informants using purposive sampling. Data collection techniques using interviews, observation and documentation. Data analysis was using data reduction techniques, data presentation and drawing conclusions. The results showed that the market relocation policy implementation was carried out through the socialization, structuring and controlling stages. However, in the relocation implementation, there are some traders who return to the old market. The neglect of the lack of compliance by some traders raises the assumption that the Regional Government is inconsistent in implementing the policies that have been issued. Judging from the principles of good governance, the local government where the research was conducted has only applied three principles, namely participation, transparency and accountability. The research results also show that the lack of facilities and infrastructure, low compliance of traders and the impression of inconsistency of the government in implementing policies that have been issued are the obstacles of these policies implementation.